Help or hindrance? The evolutionary impact of whole-genome duplication on immunogenetic diversity and parasite load - Bell, Ellen A.; Cable, Jo; Oliveira, Claudio [UNESP]; Richardson, David S.; Yant, Levi; Taylor, Martin I. (Wiley, 2020)
Whole-genome duplication (WGD) events occur in all kingdoms and have been hypothesized to promote adaptability. WGDs identified in the early history of vertebrates, teleosts, and angiosperms have been linked to the large-scale diversification of these lineages. However, the mechanics and full outcomes of WGD regarding potential evolutionary impacts remain a topic of debate. The Corydoradinae are a diverse subfamily of Neotropical catfishes with over 170 species described and a history of WGDs. They are divided into nine mtDNA lineages, with species coexisting in sympatric—and often mimetic—communities containing representatives of two or more of the nine lineages. Given their similar life histories, coexisting species of Corydoras might be exposed to similar parasite loads and because of their different histories of WGD and genome size they provide a powerful system for investigating the impacts of WGD on immune diversity and function in an animal system. Here, we compared parasite counts and the diversity of the immune-related toll-like receptors (TLR) in two coexisting species of Corydoras catfish (C. maculifer and C. araguaiaensis), one diploid and one putative tetraploid. In the putative tetraploid C. araguaiaensis, we found significantly lower numbers of parasites and significantly higher diversity (measured by both synonymous and nonsynonymous SNP counts) in two TLR genes than in the diploid C. maculifer. These results provide insight into how WGD may impact evolution, in this case by providing greater immunogenetic diversity.
Keywords: immunogenetic diversity; infectious disease; sympatric communities; toll-like receptors; whole-genome duplication